Incidence, clinical, risk factors and outcomes of Guillain‐Barré in Covid‐19. Issue 3 (28th December 2020) - Fragiel, Marcos; Miró, Òscar; Llorens, Pere; Jiménez, Sònia; Piñera, Pascual; Burillo, Guillermo; Martín, Alfonso; Martín‐Sánchez, Francisco J.; García‐Lamberechts, Eric J.; Jacob, Javier; Alquézar‐Arbé, Aitor; Juárez, Ricardo; et al.
Abstract : We diagnosed 11 Guillain–Barré syndrome (GBS) cases among 71, 904 COVID patients attended at 61 Spanish emergency departments (EDs) during the 2‐month pandemic peak. The relative frequency of GBS among ED patients was higher in COVID (0.15‰) than non‐COVID (0.02‰) patients (odds ratio [OR] = 6.30, 95% confidence interval [CI] = 3.18–12.5), as was the standardized incidence (9.44 and 0.69 cases/100, 000 inhabitant‐years, respectively, OR = 13.5, 95% CI = 9.87–18.4). Regarding clinical characteristics, olfactory–gustatory disorders were more frequent in COVID‐GBS than non‐COVID–GBS (OR = 27.59, 95% CI = 1.296–587) and COVID–non‐GBS (OR = 7.875, 95% CI = 1.587–39.09) patients. Although COVID‐GBS patients were more frequently admitted to intensive care, mortality was not increased versus control groups. Our results suggest SARS‐CoV‐2 could be another viral infection causing GBS. ANN NEUROL 2021;89:598–603